Identify User Behavior based on Tweet Type on Twitter Platform using Agglomerative Hierarchical Clustering - Prawiro Weninggalih; Yuliant Sibaroni (STMIK Budi Darma, 2022)
Information dissemination can occur through any media, including social media. One of the social media that has become a forum for disseminating information is Twitter. Through user-uploaded tweets, not a few comments are positive (praise/support) or negative (blasphemy), depending on the tweet. This study chooses politics as a discussion. Data crawling was carried out to obtain a dataset and raise the topic of Joko Widodo as a President of Indonesia, whose work is considered poor by the public, so they want him to resign immediately. This makes it interesting because we can identify user behavior from tweets about the topic. The choice of this topic was based on a lot of users who discussed it, so it was trending on Twitter. Preprocessing stage aims to eliminate missing values. After that, it then goes through the feature extraction process. The agglomerative Hierarchical Clustering Algorithm of the clustering method is applied in this research. This algorithm can directly set how many clusters to facilitate the clustering process. The result obtained 3 clusters with different user behavior. Negative user behavior is found in cluster 1, while positive user behavior is found in cluster 2.